Educação de Jovens e Adultos: currículo e formação de professores em uma escola pública da cidade de São Paulo - Silva, Tânia Regina da (2021)
The main objective of this dissertation is to analyze the implementation of the YAE Curriculum in the continuing education of teachers who work in the Elementary School. The research was developed from the following problematic: how to develop teacher training considering the conception of curriculum of the Municipal Education Secretary of the City of São Paulo for YAE, guiding the Political Pedagogical Project and the teaching practice, having as reference the profile of young people, adults and elderly. Municipal Elementary School. To this end, official documents of an Municipal Elementary School in the City of São Paulo were analyzed, such as: Political Pedagogical Project, Strategic Action Project, Pedagogical Coordinator training plan and legislation related to YAE, verifying from these records how the concepts present therein are constituted and articulated, interfering or not in the quality of education of this education modality. The research is based on the following theoretical framework: Sacristan, J.G. (2015); Di Pierro, M.C. e Haddad, S. (2000); Feldmann, M.G. (2009); Tardif, M. (2014); Arroyo, M.G. (2013); Gadotti, M., Freire, P. (1996); Saviani, D. (2013) e Silva, T.T. (2019). The methodology adopted is qualitative in approach, incorporating theoretical studies and document analysis related to Youth and Adult Education, including legislation and institutional documents and also the empirical study carried out through a questionnaire and a semi-structured script for field research. The results answer the problem by highlighting the importance of a teacher training based on interdisciplinarity and transdisciplinarity, based on the concept of a reflective teacher about the pedagogical practice and its development in discussions about cultural and identity issues, which are identified and correlated to the daily life of YAE subjects, from the organization of the Collective Pedagogical Work, allowing everyone to be involved in relevant issues in relation to real situations that affect the school community as a whole. It encourages the participation and collective action of those involved in the work at all stages of the school project, in a critical and responsible way